Depression, violence and cortisol awakening response: a 3-year longitudinal study in adolescents. Issue 6 (17th July 2018) - Yu, Rongqin; Branje, Susan; Meeus, Wim; Cowen, Philip; Fazel, Seena
Abstract: Background: Despite evidence of links between depression and violent outcomes, potential moderators of this association remain unknown. The current study tested whether a biological marker, cortisol, moderated this association in a longitudinal sample of adolescents. Methods: Participants were 358 Dutch adolescents (205 boys) with a mean age of 15 years at the first measurement. Depressive symptoms, the cortisol awakening response (CAR) and violent outcomes were measured annually across 3 years. The CAR was assessed by two measures: waking cortisol activity (CAR area under the curve ground) and waking cortisol reactivity (CAR area under the curve increase). Within-individual regression models were adopted to test the interaction effects between depressive symptoms and CAR on violent outcomes, which accounted for all time-invariant factors such as genetic factors and early environments. We additionally adjusted for time-varying factors including alcohol drinking, substance use and stressful life events. Results: In this community sample, 24% of adolescents perpetrated violent behaviours over 3 years. We found that CAR moderated the effects of depressive symptoms on adolescent violent outcomes ( β s ranged from −0.12 to −0.28). In particular, when the CAR was low, depressive symptoms were positively associated with violent outcomes in within-individual models, whereas the associations were reversed when the CAR was high. Conclusions: Our findings suggest that the CAR should be investigated further as a potential biological marker for violence in adolescents with high levels of depressive symptoms.